Potential of Gypsum Waste as a Substitution and Filler Material in Concrete Manufacturing - Fithriyah Patriotika; Sahrul Harahap; Alvi Sahrin Nasution; Muhammad Rahman Rambe; Rizky Febriani Pohan (Fluida, 2023)
Gypsum is a dental and construction material that used only at certain times. Gypsum waste can be mixed with food waste so that it endangers the environment. The gypsum waste needs to be separated and recycled. This study examines the potential use of gypsum waste as substitute and filler material in concrete manufacture, including: gypsum characteristic based on XRF, concrete maximum load, concrete compressive strength, concrete water absorption and heavy metal concentration analysis. Gypsum compositions used is 0%, 10%, 20%, 30%, 40% and 50%. The gypsum characterization results showed that there was 98.92% oxide, gypsum was included in type III gypsum, heavy metals such as: Fe = 10 ppm and Al = 16500 ppm, metallic elements such as: Si = 1950 ppm, Ca = 182900 ppm, Mg = 4560 ppm, K = 2200 ppm, and non-metallic elements namely: P = 580 ppm. The highest and lowest of maximum load and concrete compressive strength in the gypsum use as substitute and filler material are produced at the addition of 50% and 10% gypsum, respectively. The gypsum addition as substitute or filler material reduces the concrete water percentage. The heavy metals concentrations resulting from the 28-day-old concrete immersion were: Fe = <0.084 ppm and Al = <0.156 ppm.